The Fractured Jurisdiction of the Courts in Income Tax Disputes - Lubetsky, Michael H (Tax disputes in Canada: the path forward, 2022)
"The tax dispute resolution system in Canada is in need of reform. Despite the best intentions of stakeholders, it remains inefficient, expensive, and fragmented, especially in relation to significant and complex disputes. Although much public policy discussion has been devoted to substantive elements of the Canadian tax system, relatively little debate and scholarship has tackled the largely antiquated process for resolving tax disputes. This book is intended to spark a dialogue about the need for change and outline the path forward."– Provided by publisher
OCLC: 1343199509